The analysıs of the color revolutıons under the lıght of revolutıonary theorıes : the case of Kyrgyzstan - Beyribey, Tuncer (My University, 2014)
DEVRİM TEORİLERİ IŞIĞI ALTINDA RENKLİ DEVRİMLERİN ANALİZİ: KIRGIZİSTAN ÖRNEĞİ Beyribey, Tuncer Yüksek Lisans, Siyaset Bilimi ve Uluslararası İlişkiler Danışman: Yrd. Doç. Dr. EmreErşen Temmuz 2014 Bu tezin amacı, devrim teorileri çerçevesinde renkli devrimleri incelemektir. Bu amaçla Kırgızistan’da gerçekleşen Lale Devrimi örnek olay olarak seçilmiştir. Tezde renkli devrimlerin belli özelliklerine bakarak teoriler geliştirmek yerine daha kapsamlı bir inceleme yapılması gerektiği iddia edilmektedir. Bu kapsamda renkli devrimlerin tüm özelliklerini kavrayabilmek amacıyla devrim teorilerindeki yapısal ve kültürel özellikleri bir araya getiren kapsayıcı bir yaklaşım tercih edilmiştir. Bu nedenle özellikle devrimlere getirdiği süreçsel yaklaşım sebebiyle Charles Tilly'nin teorisi bir başlangıç noktası olarak alınmış ve Tilly’nin teorisi diğer yapısal ve kültürel yaklaşımlar ile zenginleştirilmiştir. Renkli devrimler ve Arap Baharı gibi yeni devrimsel olayları anlayabilmek için yapısal ve kültürel yaklaşımları birleştiren yeni bir devrim teorisi yaklaşımına ihtiyaç olduğu sonucuna ulaşılmıştır. Devrim Teorileri, Renkli Devrimler, Lale Devrimi, Charles Tilly

THE ANALYSIS OF THE COLOR REVOLUTIONS UNDER THE LIGHT OF REVOLUTIONARY THEORIES M.A., epartment of Political Science and International Relations Supervisor: Assist. Prof. Emre Erşen July 2014 This thesis examines the color revolutions from the perspective of the revolutionary theories. The Tulip Revolution is chosen as the case study for this thesis. The main argument is that a comprehensive perspective should be applied to the color revolutions, since these revolutions cannot be understood only by looking at the specific features of their emergence. Thus, this thesis aims to develop an inclusive approach that combines the structuralist and cultural approaches of revolutionary theories in order to cover up all the elements of the color revolutions. To this end, Charles Tilly's theory is selected as the basis because of its approach to revolutions as a process and also because this thesis aims to enrich Tilly’s theory by adding cultural and structuralist features. The conclusion of the thesis is that a new approach that combines both structural and cultural elements in the revolutionary theories should be developed in order to understand the new revolutionary phenomena such as the color revolutions and the Arab Spring. Revolutionary Theories, Color Revolutions, Tulip Revolution, Charles Tilly